SOSIALISASI PENGGUNAAN TANAMAN REFUGIA SEBAGAI PENOLAK HAMA DI DESA BULUMARGI, KECAMATAN BABAT, KABUPATEN LAMONGAN - Inayah Fitri,; Trisnani Alif,; Fita Fitriatul Wahidah,; Yustika Aulia Rahma,; Sitti Nur Ilmiah,; Slamet Ifandi,; Nur Habibatur Rohmah, (TAAWUN, 2021)
The problem faced by farmers in Bulumargi village, Babat district, Lamongan Regency is pest attack. Pest attack control carried out by farmers using synthetic pesticides. The use synthetic pesticides if carried out continuously gives impacts such as pest resistance, pest resurgence, death of onotarger animalincluding natural enemies, emergence of secondary pest explosions, pesticide residues in plant and environment. Synthetic pesticide residues found in agricultural products very dangerous if consumed for a long period of time, so a solution is needed that can reduce farmers' losses due to pests on crops. The purpose of this research is to eradicate pests using refugia plants. The research method used was socialization with several stages, counseling, discussions and aplications in rice fields. The result of this research is that the community has increased their knowledge and skills in the use of refugia plants. The conclusion of this research is the increasing public knowledge in utilizing refugia plants to reduce the use of synthetic pesticides and increase rice production in the long term.